EXTENSION OF HOMOTOPY PERTURBATION METHOD FOR SOLVING NONLINEAR SYSTEMS - Khirallah, Mustafa.Q.; Hafiz, M.A. (European Scientific Journal, ESJ, 2013)
In this paper, a homotopy perturbation method (HPM) is extended and applied for solving system of nonlinear equations of n-dimensional with n-variables. Also, numerical examples are used to show the performance of the presented method, on a series of examples published in the literature, and to compare with other literature methods.